Photocatalytic decomposition of fatty stains by TiO2 thin films - Juan Peris Vicente; Thierry Gacoin; Philippe Barboux; Jean-Pierre Boilot; Mauricette Rondet; Léthicia Guéneau (International Journal of Photoenergy)
Anatase TiO2 nanoparticles have been prepared as aqueous colloidal solutions by a conventional sol-gel process. Thin films have been deposited onto glass substrates by dip-coating and eventually further crystallized by heat-treatment up to 300∘C. The effect of the TiO2 film thickness, porosity and particle size on the reaction kinetics has been studied as well as the starting thickness of the fatty acid layer. The photocatalytic activity of the films has been measured through the decomposition of artificial stains formed by fatty acids deposited onto the TiO2 layer (adipic or stearic acid). The kinetics of stain photodecomposition has been studied in details by in-situ infrared spectroscopy absorption studies. This allows to discuss the role of UV light absorption and the interdiffusion of radicals and oxygen across the interfaces. The mechanism for stain decomposition is shown to be associated to a shrinkage of the solid film at the surface of the porous oxide film after a diffusion of the excited radicals from the oxide.